1980
DOI: 10.1126/science.7367881
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Characteristics of Adult Female Mice Are Correlated with Their Blood Testosterone Levels During Prenatal Development

Abstract: Mice produce litters containing many pups, and the female fetuses that develop between male fetuses have significantly higher concentrations of the male sex steroid testosterone in both their blood and amniotic fluid than do females that develop between other female fetuses. These two types of females differ during later life in many sexually related characteristics. Thus, individual variation in sexual characteristics of adult female mice may be traceable to differential exposure to testosterone during prenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
2
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(150 citation statements)
references
References 17 publications
3
142
2
3
Order By: Relevance
“…In case of rodents such as mice and rats, direct measures of prenatal T levels show that T can transfer between littermates (e.g. vom Saal and Bronson, 1980;Even et al, 1992). In line with this, rodents that developed between male fetuses differ from rodents that developed between female fetuses in several aspects (Ryan and Vandenbergh, 2002).…”
Section: Testosterone Transfermentioning
confidence: 91%
“…In case of rodents such as mice and rats, direct measures of prenatal T levels show that T can transfer between littermates (e.g. vom Saal and Bronson, 1980;Even et al, 1992). In line with this, rodents that developed between male fetuses differ from rodents that developed between female fetuses in several aspects (Ryan and Vandenbergh, 2002).…”
Section: Testosterone Transfermentioning
confidence: 91%
“…Quantitative examination of androgens in fetal rats shows that males and females have similar androgen content during much of gestation (Baum et al 1991;Weisz and Ward 1980). However, concentrations of androgens in males increase significantly late in gestation (Baum et al 1991;Houtsmuller et al 1995;vom Saal and Bronson 1980;Weisz and Ward 1980), reaching a peak around the critical developmental window of GDs 18-19 (Baum et al 1991). Several studies have suggested that this brief exposure to elevated androgens late in gestation sensitizes the developing male to androgen exposure during the neonatal period (Baum et al 1990;Hoepfner and Ward 1988;Tobet and Baum 1987).…”
Section: Natural Variation In Androgen Concentrations During Developmentmentioning
confidence: 99%
“…The IUP refers to the random positioning of fetuses in utero such that a fetus can develop between two females (0M), a male and a female (1M), or between two males (2M). In these two species, the sex of the neighboring fetuses affects exposure to androgens and estradiol of the developing fetus (Clark et al 1991;vom Saal and Bronson 1980). Females that develop between two males (2M females) are exposed to higher levels of androgens than females that develop between two females (0M females).…”
Section: Natural Variation In Androgen Concentrations During Developmentmentioning
confidence: 99%
“…While we have advanced from the simplistic 'genes as adjectives' interpretation for behavioral analyses, we have yet to explore the contribution of the dynamics within the natal nest. Not only is the sex ratio of the litter an issue [108,89,18], but the ratio of the various genotypes is equally important variable, particularly in model systems that are the result of the mating of heterozygotes (HTZ) to yield litters of varying numbers of wildtype (WT), HTZ, and knockout (KO) young of both sexes (Fig. 2).…”
Section: Effects Of Sex Ratio and Genotype Ratio Of The Litter Influementioning
confidence: 99%